Effects of Wrist Posture and Fingertip Force on Median Nerve Blood Flow Velocity. (13th February 2017) - Wilson, Katherine E.; Tat, Jimmy; Keir, Peter J.
Abstract : Purpose . The purpose of this study was to assess nerve hypervascularization using high resolution ultrasonography to determine the effects of wrist posture and fingertip force on median nerve blood flow at the wrist in healthy participants and those experiencing carpal tunnel syndrome (CTS) symptoms. Methods . The median nerves of nine healthy participants and nine participants experiencing symptoms of CTS were evaluated using optimized ultrasonography in five wrist postures with and without a middle digit fingertip press (0, 6 N). Results . Both wrist posture and fingertip force had significant main effects on mean peak blood flow velocity. Blood flow velocity with a neutral wrist (2.87 cm/s) was significantly lower than flexed 30° (3.37 cm/s), flexed 15° (3.27 cm/s), and extended 30° (3.29 cm/s). Similarly, median nerve blood flow velocity was lower without force (2.81 cm/s) than with force (3.56 cm/s). A significant difference was not found between groups. Discussion . Vascular changes associated with CTS may be acutely induced by nonneutral wrist postures and fingertip force. This study represents an early evaluation of intraneural blood flow as a measure of nerve hypervascularization in response to occupational risk factors and advances our understanding of the vascular phenomena associated with peripheral nerve compression.